First record of parasitism of scarletheaded blackbird (Amblyramphus holosericeus) by the specialized screaming Cowbird (Molothrus rufoaxillaris) - Mermoz, Myriam Emilia (2021)
Screaming Cowbird (Molothrus rufoaxillaris) is highly specialized parasitizing only three species, making records of new hosts very informative. During 2017 we studied nesting success on roadsides in Argentine Pampas. Fifty-seven nests (46%) belonged to the known host Brown-and-yellow Marshbirds (Pseudoleistes virescens). Four nests belonged to Scarlet-headed Blackbird (Amblyramphus holosericeus); one contained a Screaming Cowbird nestling that fledged with two of the host. We discuss similarities and differences among the Scarlet-headed Blackbird and old hosts. More studies are needed to confirm the regular parasitism of Scarlet-headed Blackbird by Screaming Cowbird, and to better understand their high specificity in host selection.